Surge-Type Glaciers in the Tien Shan (Central Asia). Issue 1 (1st February 2017) - Mukherjee, K.; Bolch, T.; Goerlich, F.; Kutuzov, S.; Osmonov, A.; Pieczonka, T.; Shesterova, I.
ABSTRACT: Surge-type glaciers have been observed in several mountain ranges of the world. Though Karakoram and Pamir are the hot spots for the occurrence of surge-type glaciers in High Mountain Asia, few surge-type glaciers also exist in Tien Shan. These have not been studied or reported in detail in the recent literature. We have identified 39 surge-type glaciers and five tributary surges in Tien Shan either from available literature or by visual interpretation using available images from the period 1960 until 2014. Out of the 39 glaciers, 9 are confirmed as surge-type, 13 are very probably surge-type, and the remaining are possibly of surge-type. Most of the surge-type glaciers are located in Ak-Shiirak and Central Tien Shan. Compared with the normal glaciers of Tien Shan, the surge-type glaciers are larger, cover higher ranges of elevations, and have shallower slopes. There is no significant difference in aspect. The largest surge events were observed in Central Tien Shan: North Inylchek Glacier (years 1996/1997) and Samoilowich Glacier (years 1992 until 2006) advanced several kilometers. The surge cycle was around 50 years for both of these glaciers. The advance was less pronounced for all other surge-type glaciers during the period ca. 1960–2014. Some of the tributary glaciers behaved differently than the main glaciers in the sense that they continuously advanced during the entire period of our study, whereas the main glaciers have remained stable or retreated.